Ameloblastoma radiographic imaging on 3D CBCT: a literature review - Uke, Waode Anita Wulanduri; Yunus, Barunawaty (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This review article is aimed to provide an overview of 3D CBCT in determining the diagnosis of ameloblastoma. Review: This study is a literature review consisting of English articles about the ameloblastoma radiographic imaging on 3D CBCT, published 2013-2023.The article search databases used were Google scholar, Ebsco, Pubmed .The total search results for articles based on keywords obtained were 552 articles, and only 9 articles were include. Ameloblastoma is a persistent and locally invasive tumor; with aggressive but docile growth characteristics. Ameloblastoma is generally associated with impacted teeth, so it requires a more detailed radiographic examination. Computed cone-beam tomography (CBCT) is a more advantageous imaging system with a lower radiation dose and smaller area requirements. 3D CBCT is a radiographic examination with a high modality, so it is very important in helping to establish a diagnosis, especially for cases that show radiographic differences. Ameloblastoma is divided into several types based on the radiological picture. Odontogenic Keratosis Cysts and ameloblastoma may exhibit similar radiographic features, which make diagnosis difficult. Conclusion: 3D CBCT examination is helpful in diagnosing and validating the treatment of ameloblastoma.